Phosphorescent wax - The novel approach of innovation - N Sanjana Devi; Deepak Nallaswamy Veeraiyan; Vinay Sivaswamy; Subhabrata Maiti; Dhanraj M Ganapathy; Vaishnavi Rajaraman (Wolters Kluwer Medknow Publications, 2022)
The present invention relates to dental compositions that include a phosphorescent material, more particularly, adding phosphorescent material to waxes that used in dentistry. The aim of the study is to develop a wax that has innate phosphorescent properties. Three groups of samples were taken in which the phosphorescent material was added. Three groups were later compared for their phosphorescent property in the material. All the samples in the initial molten state were poured into a mold made of silicone impression material and allowed to set. The material was placed in a dark room, and visual examination was done to compare the materials. From the samples obtained, paraffin wax showed more phosphorescent property than beeswax. The least phosphorescent property was seen in marginal wax. It can be concluded from this study that paraffin wax showed the most phosphorescent property.